Facile and green synthesis of pullulan derivative-stabilized Au nanoparticles as drug carriers for enhancing anticancer activity. (15th October 2018) - Laksee, Sakchai; Puthong, Songchan; Kongkavitoon, Pornrat; Palaga, Tanapat; Muangsin, Nongnuj
Graphical abstract: Highlights: Facile and green fabrication of cationic AuNPs using PABA-QP were firstly presented. New opportunity of cationic PABA-QP as a reducing/stabilizing/capping agent was proposed. Monodispersed AuNPs are non-toxic to normal cells and excellent intracellular uptake. DOX loaded on AuNPs@PABA-QP showed more efficacy than DOX in tested cancer cells. DOX-AuNPs@PABA-QP exhibited increasing late-apoptosis and cell arrest at S/G2-M phases. Abstract: In this work, we report for the first time AuNPs reduced/stabilized/capped with modified para -aminobenzoic acid-quat188-pullulan (PABA-QP) as excellent nanocarriers for delivery of doxorubicin to enhance the activity and safety of these systems. Spherical AuNPs@PABA-QP obtained by facile and green synthesis under optimum conditions were characterized by UV-VIS, TEM, EDS, SAED, XRD, ATR-FTIR and zeta-potential analyses and showed a narrow size distribution of 13.7 ± 1.9 nm. DOX was successfully loaded onto AuNPs@PABA-QP via intermolecular interactions with high drug loading. DOX-AuNPs@PABA-QP (IC50 = 0.39μM) showed a 2.1-fold higher cytotoxicity against Chago cells than DOX alone (IC50 = 0.82μM), while exhibiting less cytotoxicity against normal cells (Wi-38). Moreover, DOX-AuNPs@PABA-QP also demonstrated high intracellular uptake by endocytosis, arrested in S and G2-M phases of the cell cycle (total S/G2-M increased to approximately 18.0%), induced excellent cytotoxicity, and increased the fraction of late-apoptotic cells (18.6%). Consequently, it is suggested that the novel combination of DOX-AuNPs@PABA-QP has the potential to be developed for human cancer treatment.